The Patient Care and Complications of Hemodialysis Procedure for Renal Failure Patients: A Descriptive Study at al Nasiriya city, South of Iraq - Firas Fadhil Alyassin (Journal of Global Pharma Technology, 2018)
Objective: the aim of this study is to describe the side effects and complications of renal failure and hemodialysis procedure. It also evaluates the general clinical care and nursing interventions for hemodialysis patients treated at the artificial kidney unit in Al Hussein-teaching hospital. Subjects and methods: this study is performed in Al-Hussein teaching hospital in Al-Nasiriya city, south of Iraq from October 1st, 2015 to May, 2016. Eighty patients [(54) males and (26) females], age (10 – 85 years) and were enrolled in this study. All of the patients were diagnosed with renal failure by specialist doctors and currently on hemodialysis renal replacement therapy. The data collected from patients through a questionnaire list designed and developed for this study. The list concerned with the adverse effects, complications, mortality and morbidity related data in addition to the patients' general information. The collected results were analyzed in order to construct tables, figures and other necessary research requirements. Results and conclusions: in this study, most of the hemodialysis cases are caused by hypertension (37.5%). The most common complications in hemodialysis patients were edema (78.75%), anemia (63.75%), and arterial hypertension (60%). The most common side effects associated with hemodialysis procedure were nausea and vomiting (47.5%) , dyspnea (21.25%) and headache (25%). The major treatments and diets of patients in this study were erythropoietin injection (66.25%), protein restriction (86.25%) and restriction fluid (77.5%). The clinical care and nursing interventions for hemodialysis patient enrolled in this study were relatively good according to the results (82%).Keywords:Hemo dialysis, Renal failure, Nasiriya city, Iraq